(untitled) (Journal of the Management Sciences, 2024)
This study was informed by the lack of savings or inadequate savings mobilization as well as loan disbursement among members of Investment and Credit Cooperative Societies in Kaduna State. The study specifically examined the rate of savings mobilized among members of Investment and Credit Cooperative Society and the amount of loans granted to members of Investment and Credit Cooperative Society. The study was anchored on Financial Intermediation theory. The study adopted a survey research design with a population of 4,334 of members of Investment and Credit cooperative in Kaduna State. Questionnaire was developed by the researcher, based on the Likert 5 -point and was used to gather the data. Multi-stage sampling technique was adopted. Frequencies and simple percentages were used to analyze the respondent bio data while mean score was used based on the research questions. Findings revealed that majority of the members of investment and credit cooperative society save within N20, 000.00 to N50, 000.00 every month with a mean rating of (X = 4.20). Findings also revealed that that members received short-term loan between the range of N20, 000.00 to N50, 000.00 with a mean rating of (X = 4.00). It was recommended among others that members should be encouraged to save more so as to provide more loans for needy members. Also, the bureaucratic process of getting cooperative loan should be reduced so as not to discourage members from collecting loans.